Pre-Operative Depression and Anxiety in Patients Undergoing Open-Heart Surgery - Arnengsih Nazir; Lynna Lidyana; Faresha Nadia Amanda; M. Maulana Efry (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
ABSTRACT Introduction: Cardiac disease and mental health are two related disorders and often co-exist together. As one of the interventions to manage patients with cardiac diseases, the heart surgical procedure also correlated with depression and anxiety which will interfere with the prognosis. This study aimed to know the incidence of depression and anxiety in patients before undergoing open-heart surgery at Dr. Hasan Sadikin General Hospital (RSHS) Bandung. Methods: This study was a case series using primary data from patients and secondary data from medical records. Subjects were adult patients who will undergo open-heart surgery at RSHS Bandung. Data collection was started from November to December 2019. Variables assessed were depression and anxiety. Demographic profiles (age, gender, occupation, education, and marital status), as well as medical profiles (underlying disease, comorbidity, and type of surgical procedure), were also obtained. Results: Seven subjects will undergo open-heart surgery during the study period. One subject was excluded for returning an incomplete questionnaire. Subjects’ age was ranged from 28–58 years with a 1:1 male to female ratio. Subjects were dominated by those who will undergo mitral valve replacement(4 of 6). No subject had depression and anxiety in this study. Discussion: In this study, no incidence of depression and anxiety were found among subjects. The possible explanation for this result was the dominant underlying disease of valvular heart disease which was known to have a lower incidence of psychological disorders compared to coronary artery disease. Conclusion: Depression and anxiety were not found among the subjects of th is study.Keywords: anxiety, coronary artery disease, depression, heart disease, open-hear t surgery